Analysis of spur gearbox dynamics considering tooth lubrication and tooth crack severity progression. (February 2023) - Yang, Xingkai; Tofighi-Niaki, Ebrahim; Zuo, Ming J.; Tian, Zhigang; Safizadeh, Mir Saeed; Qin, Dali
Abstract: A novel tribo-dynamic model of a spur gearbox considering both tooth lubrication and tooth crack is proposed, which integrates an elastohydrodynamic lubrication (EHL) model of a spur gear pair into a gearbox lumped parameter model. The combined stiffness and combined damping of a spur gear pair with a tooth crack are obtained using the oil film stiffness and oil film damping provided by the EHL model and the tooth mesh stiffness and tooth mesh damping calculated by the potential energy method. Effects of tooth lubrication and tooth crack severity progression on combined stiffness, combined damping, and gearbox vibration responses are studied. It is found that considering the tooth lubrication in gearbox dynamic modeling leads to a backward shift of the frequency components induced by tooth crack. A comparison has been made between the proposed tribo-dynamic model and the conventional model of a spur gearbox, and the effectiveness of RMS and Kurtosis for tracking tooth crack severity progression is investigated in the presence of tooth lubrication. The comparison results reveal that the consideration of tooth lubrication overall reflects tooth crack signatures better.